2013
DOI: 10.4037/ccn2013341
|View full text |Cite
|
Sign up to set email alerts
|

From Door to Recovery: A Collaborative Approach to the Development of a Post–Cardiac Arrest Center

Abstract: Out-of-hospital cardiac arrest remains common and, despite advances in resuscitation practices, continues to carry a high mortality that may be influenced by several factors, including where a patient is cared for after the cardiac arrest. Implementing a post–cardiac arrest care guideline for survivors of out-of-hospital and in-hospital cardiac arrest involves a multidisciplinary approach with short-term and long-term strategies. Physician and nursing leaders must work in synergy to guide the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The implementation of institution-specific standardized protocols, order sets, and a bundled care approach have proven a successful method in combating the barriers to implementation of therapeutic hypothermia [14][15][16][17][18][19][20] and were associated with an increased efficiency in achieving target temperature. 21,22 The effectiveness of a surgical safety checklist on rates of postoperative death and complications was documented by Haynes et al, 23 who reported a decrease in death rate and complication rate after implementation of a checklist.…”
Section: Recommendations For the Use Of Checklistsmentioning
confidence: 99%
“…The implementation of institution-specific standardized protocols, order sets, and a bundled care approach have proven a successful method in combating the barriers to implementation of therapeutic hypothermia [14][15][16][17][18][19][20] and were associated with an increased efficiency in achieving target temperature. 21,22 The effectiveness of a surgical safety checklist on rates of postoperative death and complications was documented by Haynes et al, 23 who reported a decrease in death rate and complication rate after implementation of a checklist.…”
Section: Recommendations For the Use Of Checklistsmentioning
confidence: 99%